Cosmic birefringence from monodromic axion dark energy. Issue 8 (1st August 2022) - Gasparotto, Silvia; Obata, Ippei
Abstract: The recently reported non-zero isotropic birefringence angle in Planck 2018 polarization data provides a tantalizing hint for new physics of axions. In this paper, we explain this by a string theory motivated axion with a monodromy potential that plays the role of dark energy. Upon using the birefringence measurement and the constraint on the equation of state for dark energy in this scenario, we find an upper bound on the axion decay constant as fa ≲ 10 16   GeV. This naturally gives an energy scale of order GUT and can resolve the theoretical issue of super-Planckian field range of the conventional axion dark energy model. We further study the implications of cosmic birefringence for the underlying theory and its consequences for the string swampland conjectures. We finally discuss oscillatory features in the dark energy sector and the expected cosmic birefringence tomography.